La controversia Pani-De la Huerta ¿crisis fiscal o artificio político? - Lomelí Vanegas, Leonardo (El Colegio de México, A.C., 2022)
In the summer of 1923, the presidential succession was decided in favor of Plutarco Elías Calles and the definitive rupture of the so-called Sonoran Triangle occurred. Although he formally supported Calles’s candidacy, Finance Secretary Adolfo de la Huerta confronted both Calles and President Álvaro Obregón in order to defend those who had supported his candidacy and resigned. His successor, Alberto J. Pani, presented an alarming report on the state of the Finance Secretariat, provoking a controversy in which De la Huerta aimed to defend his work and Pani to prove that the country was on the verge of bankruptcy. The backdrop to this controversy was De la Huerta’s acceptance of his presidential candidacy and its abrupt end was due to the De la Huerta Rebellion. Nearly one hundred years later, there are still doubts about the seriousness of the fiscal crisis reported by Pani. This article explains the development of the controversy, the arguments given by each party and the intervention of other political actors, concluding that, while the nation’s finances were not in good shape, the situation was exaggerated in order to politically discredit Adolfo de la Huerta.